Expression of molecular markers of peripheral blood lymphocyte activation before and after eye-preserving treatment for choroidal melanomas of various stages (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the expression of molecular markers of peripheral blood lymphocyte activation (СD7+, CD54+, CD95+) before and after eye-preserving treatment for Т1 to Т3  choroidal melanoma (CM).Material and Methods: Expression of molecular markers of peripheral blood lymphocyte activation (СD7+, CD54+, CD95+) was examined before and after eye-preserving treatment for Т1 to Т3 CM. The major study group (group 1) consisted of 25 patients (14 (56.0%) women and 11 (44.0%) men; mean age (standard deviation (SD)), 51.7 (16.6) years) who received the eye-preserving treatment (transpupillary thermotherapy (TTT (delivered using the developed methodology) combined with strontium-90/yttrium-90 (90Sr/90Y) brachytherapy (BT)) for moderate to large (T1-T3) CM (tumor base, 3.1 to 15 mm; tumor thickness, 3.1 to 9.0 mm). The control group (group 2) consisted of 16 patients (12 (75.0%) women and 4 (25.0%) men; mean age (SD), 55.4 (11.2) years) who received TTT only for small (T1) CM (tumor base, ≤ 12 mm; tumor thickness, ≤ 3 mm).Results: The expression of markers CD7+, СD54+, and CD95+ before treatment for Т1-Т3 CM was higher than before treatment for small Т1 CM, but the difference was significant only for the absolute expression of CD7+ (р = 0.0008).After TTT for small Т1 CM, a statistically significant increase was observed only in the absolute and percentage expression of CD7+ (р = 0.04 and р = 0.0000, respectively) and the absolute expression of FAS-ligand CD95+ (р = 0.05). Additionally, the level of СD54+ increased after treatment, but not significantly. Absolute expression levels of these molecular markers decreased after TTT plus BT, but not significantly. Additionally, the percentage expression of СD7+ decreased statistically significantly (р = 0.02), and the percentage expression of СD95+ decreased statistically insignificantly (р = 0.06). After eye-preserving treatment for CM, there were significant differences between the two groups in the absolute and percentage expression of FAS-ligand CD95+ (р = 0.003 and р = 0.000, respectively) and CD54+ (р = 0.03 and р = 0.000 respectively), with these levels being lower in group 1.Conclusion: Expression of molecular markers of peripheral blood lymphocyte activation (СD7+, CD54+, CD95+) increased with tumor progression in patients with CM. The expression of the markers increased after TTT only for small Т1 CM, and decreased after TTT plus BT (90Sr/90Y) for Т1-Т3 CM, likely due to the effect of radiotherapy.
Keywords: choroid; immunology; radiotherapy, transpupillary thermotherapy; molecular markers; ophthalmic oncology; choroidal melanoma